Superheroes and third-wave feminism. Issue 3 (4th May 2018) - Curtis, Neal; Cardo, Valentina
Abstract: Recent developments in superhero comics have seen positive changes to the representation of characters and storylines. In this article, we use examples of the increase in female characters and female-led titles, the swapping of gender from a male character to a female one, and the increase in female writers and artists to investigate how the representation of female characters has evolved. We argue that these changes mark an intervention on behalf of female creators in keeping with the theory and practice of third-wave feminism. We also argue that this evolution provides a good example of how third-wave feminism remains indebted to and continues the important work of second-wave feminism. The article explores the important role of intersectionality alongside themes relating to the body and sexuality, violence, solidarity and equality, and girlhood in comics such as Birds of Prey, Harley Quinn, Ms. Marvel, Captain Marvel, and A - Force.